Sodium, Potassium Intake, and Sleep Duration Linked to Hypertension in Adults 40-60 in East Jakarta - Salsabila, Risa (Al-Hijrah Indonesia, 2024)
Hypertension is a non-communicable disease with an increasing prevalence in Indonesia, often referred to as a silent killer due to its asymptomatic nature until serious complications like stroke or kidney failure occur. This study aims to analyze the relationship between sodium intake, potassium intake, and sleep duration with hypertension among middle-aged individuals (40-60 years) in Kramat Jati Subdistrict, East Jakarta. A cross-sectional design was used, involving 97 purposively selected respondents. Data on sodium and potassium intake were collected using a 24-hour food recall method, sleep duration through structured interviews, and hypertension status through blood pressure measurements. Data were analyzed using Chi-Square and Fisher’s Exact Test. The results showed no significant relationship between sodium intake and hypertension (p = 0.218), although 75% of respondents consumed excessive sodium. Conversely, potassium intake had a significant relationship with hypertension (p = 0.047), with 71% of respondents with sufficient potassium intake being non-hypertensive. Sleep duration also showed a significant association with hypertension (p = 0.032), as respondents with less than six hours of sleep had higher blood pressure. This study concludes the importance of maintaining dietary balance by increasing potassium intake, reducing sodium, and ensuring adequate sleep duration to prevent hypertension. Public education on healthy lifestyles is recommended to lower hypertension risk in urban middle-aged populations.